Standardisation of agrotechniques in phalaenopsis orchids - Narender Negi (Department of Pomology and floriculture,College of Horticulture, 2012)
The present study entitled “Standardisation of agrotechniques in Phalaenopsis orchids” was carried out at the Department of Pomology and Floriculture, College of Horticulture, Vellanikkara from May 2011 to April 2012. The studies were conducted to find out the best plant type and environment suited for commercial cultivation of Phalaenopsis and to standardise the agrotechniques like type of pot, growing media and growing method for better plant growth and quality spikes. The study involved comparison of 32 treatment combinations involving two plant types, two types of pots, two types of potting media, two growing conditions and two methods of growing. The experiment was laid out in CRD with three replications. Various vegetative and floral characters were recorded, analysed and correlated with weather parameters. Results indicated that of the two growing structures used in the study i.e., fan and pad and rain shelter, the latter promoted vegetative growth manifested by enhanced leaf length, leaf breadth and leaf area. Plant height was not influenced in both the situation. The plant types viz., pot plant and cut flower, differed in their growth rate. Pot plant type recorded higher growth rate in terms of length, breadth and area of leaf but per se length, breadth and area of leaf was higher in cut flower type. Regarding the media, brick + coconut husk bits was found better for vegetative growth as compared to brick + charcoal. The other two factors, method of growing and type of pots did not affect the vegetative growth. But root growth outside the pot was recorded more in black pot compared to that on white pot. Percentage of flowering was also influenced by growing structure, type of plant and media. Plants grown under fan and pad, pot plant type and brick + coconut husk bits medium recorded higher flowering percentage than those under rain shelter, cut flower and brick + charcoal medium. Correlation values with weather parameters indicated positive correlation between increase in leaf area and minimum temperature under rain shelter and fan and pad system whereas negative correlation with light intensity was seen under fan and pad system. Considering the overall effect by pooled analysis, only minimum temperature had a significant influence on increase in leaf area.